2020
DOI: 10.1101/2020.08.21.262097
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compartment-Specific Neurexin Nanodomains Orchestrate Tripartite Synapse Assembly

Abstract: At tripartite synapses, astrocytes surround synaptic contacts, but how astrocytes contribute to the assembly and function of synapses remains unclear. Here we show that neurexin-1α, a presynaptic adhesion molecule that controls synapse properties, is also abundantly expressed by astrocytes. Strikingly, astrocytic neurexin-1α, but not neuronal neurexin-1α, is highly modified by heparan sulfate. Moreover, astrocytic neurexin-1α is uniquely alternatively spliced and invariably contains an insert in splice-site #4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 122 publications
3
23
0
Order By: Relevance
“…Astrocytes express high levels of Nrxn1 similar to neurons, but astrocytic Nrxn1 is primarily present as Nrxn1-SS4+ whereas neuronal Nrxn1 is a mixture of Nrxn1-SS4+ and Nrxn1-SS4– (Trotter et al, 2020 ). Examination of the Alternative Splicing and Gene Expression Summaries of Public RNAseq Data [ASCOT; http://ascot.cs.jhu.edu/ (Ling et al, 2020 )] showed that Nrxn1-SS4 is differentially spliced between neurons and astroglial cells.…”
Section: Resultsmentioning
confidence: 99%
“…Astrocytes express high levels of Nrxn1 similar to neurons, but astrocytic Nrxn1 is primarily present as Nrxn1-SS4+ whereas neuronal Nrxn1 is a mixture of Nrxn1-SS4+ and Nrxn1-SS4– (Trotter et al, 2020 ). Examination of the Alternative Splicing and Gene Expression Summaries of Public RNAseq Data [ASCOT; http://ascot.cs.jhu.edu/ (Ling et al, 2020 )] showed that Nrxn1-SS4 is differentially spliced between neurons and astroglial cells.…”
Section: Resultsmentioning
confidence: 99%
“…The neurexin/ neuroligin and ephrin/Eph receptor-mediated contacts between astrocytic processes and synaptic terminals have been reported to regulate astrocyte-mediated synaptic plasticity [79][80][81][82][83][84]. Of note, the deletion of Nrxn1 (neurexin-1) in astrocytes but not in neurons suppresses AMPAR-mediated excitatory postsynaptic currents (EPSCs) in CA1 pyramidal neurons of acute hippocampal slices, suggesting that astrocytic Nrxn1 interacts with neuronal neuroligins to regulate excitatory synaptic transmission through the modulation of AMPAR response [84]. Meanwhile, ephrins expressed by astrocytes regulate dendritic spine formation and elimination as well as synaptic plasticity through the activation of neuronal Eph receptors (Fig.…”
Section: Regulation Of Contact-mediated Signalingmentioning
confidence: 99%
“…The hyperfunction of a given brain region puts considerable strain on the circuit, and it seems that over the course of a lifetime, the brain keeps trying to compensate for the abnormalities that arise at different stages of HD. The recent observation that deletion of astrocytic neurexin-1α attenuates synaptic transmission but not synapse number supports this hypothesis (Trotter et al, 2020).…”
Section: Discussionmentioning
confidence: 84%